Microbiome and Metabolome Profiles Associated With Different Types of Short Bowel Syndrome: Implications for Treatment - Budinska, Eva; Gojda, Jan; Heczkova, Marie; Bratova, Miriam; Dankova, Helena; Wohl, Petr; Bastova, Hana; Lanska, Vera; Kostovcik, Martin; Dastych, Milan; Senkyrik, Michal; Krizova, Jarmila; et al. (JPEN. Journal of parenteral and enteral nutrition, 2020)
BACKGROUND: The gut microbiome and metabolome may significantly influence clinical outcomes in patients with short bowel syndrome (SBS). The study aimed to describe specific metagenomic/metabolomics profiles of different SBS types and to identify possible therapeutic targets. METHODS: Fecal microbiome (FM), volatile organic compounds (VOCs), and bile acid (BA) spectrum were analyzed in parenteral nutrition (PN)-dependent SBS I, SBS II, and PN-independent (non-PN) SBS patients. RESULTS: FM in SBS I, SBS II, and non-PN SBS shared characteristic features (depletion of beneficial anaerobes, high abundance of Lactobacilaceae and Enterobacteriaceae). SBS I patients were characterized by the abundance of oxygen-tolerant microrganisms and depletion of strict anaerobes. Non-PN SBS subjects showed markers of partial FM normalization. FM dysbiosis was translated into VOC and BA profiles characteristic for each SBS cohort. A typical signature of all SBS patients comprised high saturated aldehydes and medium-chain fatty acids and reduced short-chain fatty acid (SCFA) content. Particularly, SBS I and II exhibited low protein metabolism intermediate (indole, p-cresol) content despite the hypothetical presence of relevant metabolism pathways. Distinctive non-PN SBS marker was high phenol content. SBS patients' BA fecal spectrum was enriched by chenodeoxycholic and deoxycholic acids and depleted of lithocholic acid. CONCLUSIONS: Environmental conditions in SBS gut significantly affect FM composition and metabolic activity. The common feature of diverse SBS subjects is the altered VOC/BA profile and the lack of important products of microbial metabolism. Strategies oriented on the microbiome/metabolome reconstitution and targeted delivery of key compounds may represent a promising therapeutic strategy in SBS patients.
Keywords: feces; žlučové kyseliny a soli; Humans; lidé; gut microbiota; syndrom krátkého střeva; Gastrointestinal Microbiome; těkavé organické sloučeniny; Dysbiosis; Metabolome; Short Bowel Syndrome; dysbióza; parenterální výživa; parenteral nutrition; metabolom; Volatile Organic Compounds; Parenteral Nutrition; střevní mikroflóra; bile acids; Bacteria; Bile Acids and Salts; short bowel syndrome, short-chain fatty acids, volatile organic compounds; Feces